Keanekaragaman Manifestasi Klinis pada Coronavirus Disease 2019 (COVID-19) - Budi Yanti; T Andi Syahputra; Fitri Amalia Rahma; Rauzatil Aula Katuri; Rosi Mega Safitri (Fakultas Ilmu Kesehatan, 2020)
Abstract Coronavirus disease 2019 (COVID-19) was caused by SARS-CoV-2 and is currently a global public health problem. This disease transmits through aerosols and saliva when coughing and sneezing from a person with symptoms or carrier people. The diversity of clinical manifestations would be detected and depended on the number of ACE2 receptor expressions that are scattered throughout the human body. The more expression in the organ, the more frequent symptoms that appear in the patient. The respiratory dysfunction is the most common symptoms that will be detected and followed by the olfactory dysfunction such as anosmia, the visual dysfunction such as conjunctivitis, the digestive dysfunction such as nausea, vomiting, and diarrhea, the vascular dysfunction such as thrombosis and embolism, and the cardiovascular dysfunction such as Acute Cardiac Injury and Acute Coronary Syndrome. This review literature used an internet-based search engine method that aims to discuss functional disorders in the human body system that caused diversity of clinical manifestations in COVID-19. Key words: Diversity, Symptoms, COVID-19, SARS CoV-2